Challenges in the treatment of Iranian patients with leukemia in comparison with developed countries from the perspective of specialists - Bakhshi Biniaz, Ramin; Goudarzi, Mehdi; Sahmani, Mehdi; Moghaddasi, Mohammad Hossein; Dehghanifard, Ali; Vatanmakanian, Moosa; Azad, Mehdi (Archives of Advances in Biosciences, 2014)
Evaluation of the factors associated with treatment process of leukemia and comparison with current related approaches in developed countries can present a good indicator to assess the weak and strong points in healthcare system of our country in leukemia treatment. The objective of this research is general and specific description of the challenges and shortcomings in Iranian healthcare system and monitoring of hematologic malignancies as well as comparison with developed countries. Our study is a descriptive-cross-sectional study. 100 hemato-oncologist , pathologists, and faculty members throughout the country were selected by random cluster sampling. Data collected using questionnaires with Cronbach's alpha coefficient of 0.76 . SPSS and Chi-square test were used for data analysis. According to the specialists, lack of advanced diagnostic facilities as well as cell and BM banks together with high treatment expenses are the main factors contributing to poor treatment processes in Iran, which are far from worldwide standards.The use of novel currently methods used in developed countries for leukemia treatment, financial and psychological support of patients under treatment , making underprivileged provinces well-equipped ,balanced specialist service distribution relative to capital city either in diagnosis or treatment are factors which makes system standardized. Moreover, integrated institutional work in relation to leukemia incidence and statistical analysis of mortality and morbidity rate can pave the way for reducing and eliminating the problems in diagnosis and treatment of leukemia patients.